2022
DOI: 10.1007/s12032-022-01659-2
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of high-mobility group box 1 in B16F10 melanoma cells induced host immunity-mediated suppression of in vivo tumor growth

Abstract: High-mobility group box 1 (HMGB1) has been reported as a damage-associated molecular pattern (DAMP) molecule that is released from damaged or dead cells and induces inflammation and subsequent innate immunity. However, the role of HMGB1 in the anti-tumor immunity is unclear since inflammation in the tumor microenvironment also contributes to tumor promotion and progression. In the present study, we established HMGB1-knockout clones from B16F10 and CT26 murine tumors by genome editing using the CRISPR/Cas9 syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…On this topic, a study conducted by Yakomizo et al, showed that the knockout of HMGB1 in tumor cells converted tumors from scarcely immunogenic phenotypes to inflammation-prone-ones, de facto inhibiting in vivo tumor growth. Thus, manipulation of tumor derived HMGB1 might be applicable to improve the clinical outcome of cancer therapies, including immune checkpoint blockades and cancer vaccine therapies [ 41 ]. Highly metastatic tumor cells preferentially enter senescence and adopt survival mechanisms, while apoptosis predominates in weakly metastatic tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…On this topic, a study conducted by Yakomizo et al, showed that the knockout of HMGB1 in tumor cells converted tumors from scarcely immunogenic phenotypes to inflammation-prone-ones, de facto inhibiting in vivo tumor growth. Thus, manipulation of tumor derived HMGB1 might be applicable to improve the clinical outcome of cancer therapies, including immune checkpoint blockades and cancer vaccine therapies [ 41 ]. Highly metastatic tumor cells preferentially enter senescence and adopt survival mechanisms, while apoptosis predominates in weakly metastatic tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The B16F10‐derived HMGB1‐KO clones (G9 and A10E2) were previously established in our laboratory. 21 The linear donor was inserted around cDNA position 198 in exon 2 of the HMGB1 gene, which was 25 nucleotides downstream of the initiation codon, and all the functional domains of HMGB1 were disrupted in these KO clones. The KO cells from frozen stock were used within 1 month of in vitro culture after thawing.…”
Section: Methodsmentioning
confidence: 99%
“… 21 Our previous study 22 as well as others 23 , 24 , 25 regarding the anti‐tumor effect of HMGB1 inhibitors, suggested a possible application of suppression of tumor‐derived HMGB1 to cancer immunotherapy, such as ICB and neoantigen vaccine therapies. 21 , 22 , 23 , 24 , 25 Although most previous studies supported the negative effect of HMGB1 on anti‐tumor immunity, 21 , 22 , 23 , 24 , 25 a positive role of HMGB1 in the initiation of innate and subsequent adaptive immunity has also been shown. 26 , 27 Namely, the binding of HMGB1 to receptors, such as Toll‐like receptor (TLR)‐2, TLR‐4, and the receptor for advanced glycation end products (RAGE), on macrophages and dendritic cells induces proinflammatory cytokines through activation of interferon regulatory factor‐3 (IRF3) and subsequently triggers innate immunity.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations